Hubungan Pola Asah, Asih, dan Asuh dengan Kejadian Stunting di Wilayah Kerja Puskesmas Lontar Surabaya - Nur Astri Amelia (Universitas Airlangga, 2023)
Background: Stunting, often known as short children, is a condition in which a child's length or height is significantly below average for his or her age. Meeting children's basic needs throughout their formative years is an effective way to stop them from being stunted. Parents, and especially mothers, are responsible for seeing to their children's basic requirements. Developmental outcomes for toddlers are influenced by maternal involvement in caregiving. These fundamental requirements take the form of kindness, concern, and attention. Objectives: The purpose of this study was to analyze the relationship between the pattern of nurturing, caring and caring provided by mothers and caregivers with the incidence of stunting in the working area of the Lontar Health Center in Surabaya. Methods: This study used a case-control design, making it an analytical observational study. A total of 52 children took part in the study, and they were split evenly between two groups (the